Chicken Disease Diagnosis Expert System Using Case Base Reasoning Method in the Office Livestock and Animal Health Bengkulu City - Tommy Suriatno; Siswanto Siswanto; Yupianti Yupianti (Jurnal Komputer, Informasi dan Teknologi, 2021)
Chickens are the most widely bred livestock because of the many benefits and advantages. As with other livestock, chickens have various types of diseases. For some breeders who want to raise chickens, especially ordinary people, they are faced with several problems, one of which is disease. To diagnose the disease, the symptoms that appear on the chicken's body are needed. Seriousness and fast action are needed before it's too late and suffers losses. Therefore, the purpose of this program is to assist farmers in obtaining some information about chickens. The sooner chicken disease is detected, the sooner they can prevent it. An expert system for diagnosing chicken diseases using the Case Base Reasoning method at the Bengkulu City Office of Animal Husbandry and Health was built using the PHP programming language and MySQLi database. The application is divided into two parts, namely the general user page and the administrator or operator special admin page. The results show that the diagnosis results from the selected symptoms, the application also displays the possibility of other diseases detected based on these symptoms. In addition, there are also details of the disease, along with suggestions that must be done by farmers to the sick chickens. In addition to diagnosing diseases, this expert system application can also provide information about chicken diseases and how to handle them, as well as in all disease and symptom relationships between data from sources and the application is appropriate.